Evaluation of Effects of Staining and Bleaching Agents on the Stability of Color for Microhybrid and Nanohybrid Resin Composite Restorative Materials – An In vitro Study - Simran Virdy; Surya Dahiya; Navneet Kukreja; Rajan Dhawan; Nidhi Aggarwal; Mohini Tiwari (Journal of Pharmacy and Bioallied Sciences)
Objective: The aim of this study was to investigate the color changes (ΔE) of two different composite resins after staining and bleaching. Material and Methods: A total of 100 specimens were prepared from microhybrid and nanohybrid composites. The samples were divided into five groups and stained for 30 days with tea, coffee, cola, red wine, or distilled water (control). Each group was further divided into two subgroups to receive a 14-day application of Opalescence PF or VivaStyle® Paint On Plus bleaching materials. The color of all samples was determined at baseline, after staining, and after bleaching. Data were analyzed using ANOVA and independent sample t-test. Results: The highest ΔE values were observed in the red wine groups for both composites. Bleaching agents decreased ΔE values; however, they were unable to return the values to baseline values. Conclusion: Staining and bleaching may affect color, depending on the type, filler, and matrix content of the composite resin.